Performance enhancement of the wavy cylinder-based piezoelectric wind energy harvester with different wave-shaped attachments - Lin Zou; Yulong Yan; Diwei Liu; Xiaofan Zhang; Hao Xia (Energy Reports, 2023)
The vortex-induced vibration (VIV)-based piezoelectric wind energy harvester (PWEH) has a small working bandwidth and poor wind energy harvesting performance. In order to improve the output power of the PWEH and achieve sustainable power supply for microelectronic products, this study proposes a novel wavy cylinder-based PWEH with two wavy attachment rods attached to the surface of the wavy cylinder, the mathematical model of PWEH is developed. The flow-induced vibration (FIV) response mechanism and the energy harvesting characteristics of the wavy cylinder-based PWEH are numerically explored. The wavy cylinder with wavy-shaped attachments produces a three-dimensional shear layer that can increase the wavy cylinder’s aeroelastic instability range and realize the synergistic effects of VIV and galloping, which increases the wave cylinder’s vibrational amplitude and lowers the galloping critical wind speed. Compared with the typical VIV-PWEH, the novel wind energy harvester can work outside the VIV lock-in range, and its output power and voltage rise as wind speed does. The wavy attachment rods with triangular cross section have greater advantages than other rods, its output power is 6.13 mW at a wind speed of 5.7 m/s and load resistance of 100 KΩ, compared with the circular cylinder PWEH, the average power increases by approximately 166%. The study’s findings can theoretically promote the enhancement of PWEH’s energy harvesting efficiency.